Peran Kader Posyandu Anggrek Dalam Pemberdayaan Kesehatan Masyarakat Di Desa Olehsari Kecamatan Glagah Kabupaten Banyuwangi - Moh. As’adi; Zaki Al Mubarok; Fina Diana Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research has several objectives, including understanding the role of Posyandu Anggrek cadres in community health empowerment and the supporting and inhibiting factors of the Posyandu Anggrek cadres' role in community health empowerment in Olehsari Village, Glagah District, Banyuwangi Regency. The research method applied in this study is qualitative research. Several data collection techniques were used, including observation, interviews, and documentation. In this study, the researcher serves as the instrument. The data analysis technique used in this research is the interactive technique with steps including data collection, data display, reduction, and conclusion drawing. Meanwhile, data validity testing in this study used data triangulation and member checks. The results of this research indicate that the role of Posyandu Anggrek Cadres in community health empowerment in Olehsari Village is very important and influential. With strong support from the government, the community, and relevant institutions, as well as the enthusiasm and commitment of Posyandu Anggrek cadres, efforts to empower health in the village can successfully create a healthier, more productive, and higher quality environment for the community, especially for children experiencing stunting. Meanwhile, inhibiting factors include limited accessibility, lack of community understanding, limited resources, political and social instability, and insufficient involvement of the government and relevant institutions in carrying out the cadres' duties.